2017
DOI: 10.1016/j.cognition.2017.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Action-effect sharing induces task-set sharing in joint task switching

Abstract: A central issue in the study of joint task performance has been one of whether co-acting individuals perform their partner's part of the task as if it were their own. The present study addressed this issue by using joint task switching. A pair of actors shared two tasks that were presented in a random order, whereby the relevant task and actor were cued on each trial. Responses produced action effects that were either shared or separate between co-actors. When co-actors produced separate action effects, switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
2
9
2
Order By: Relevance
“…For instance, there are a number of studies on the joint Simon task that showed that the joint Simon effect depended on various social factors (e.g., Hommel, Colzato, & van den Wildenberg, 2009;Iani, Anelli, Nicoletti, Arcuri, & Rubichi, 2011;Ruys & Aarts, 2010). It has also been shown in joint task switching that switch cost was reinstated after the co-actor's trials when two actors shared the same action effect (Yamaguchi et al, 2017a). These observations seem to be consistent with the two-mode hypothesis of the joint task performance.…”
Section: Dividing the Labor Of The Stroop Task 20supporting
confidence: 74%
See 1 more Smart Citation
“…For instance, there are a number of studies on the joint Simon task that showed that the joint Simon effect depended on various social factors (e.g., Hommel, Colzato, & van den Wildenberg, 2009;Iani, Anelli, Nicoletti, Arcuri, & Rubichi, 2011;Ruys & Aarts, 2010). It has also been shown in joint task switching that switch cost was reinstated after the co-actor's trials when two actors shared the same action effect (Yamaguchi et al, 2017a). These observations seem to be consistent with the two-mode hypothesis of the joint task performance.…”
Section: Dividing the Labor Of The Stroop Task 20supporting
confidence: 74%
“…Previous findings support this position, showing that the actors in the joint Simon task monitor the proportion of compatible trials for their own part but not for their co-actor's part (Yamaguchi, Wall, & Hommel, 2018a) and that the actors in a joint task-switching setting do not monitor the task that their co-actor has performed on a preceding trial (Wenke et al, 2011; DIVIDING THE LABOR OF THE STROOP TASK 5 Yamaguchi, Wall, & Hommel, 2017b). Such task monitoring appears to occur under specific conditions (Dudarev & Hassin, 2016;Liefooghe, 2016;Yamaguchi, Wall, & Hommel, 2017a). Therefore, the actors may only represent limited aspects of the co-actor's part of the task, and they divide the labor of the joint task, eliminating an additional burden monitoring their co-actor's part of the task.…”
supporting
confidence: 56%
“…For instance, there are a number of studies on the joint Simon task that showed that the joint Simon effect depended on various social factors (e.g., Hommel et al, 2009 ; Ruys and Aarts, 2010 ; Iani et al, 2011 ). It has also been shown in joint task switching that switch cost was reinstated after the co-actor’s trials when two actors shared the same action effect ( Yamaguchi et al, 2017a ). These observations seem to be consistent with the two-mode hypothesis of the joint task performance.…”
Section: Discussionmentioning
confidence: 97%
“…Previous findings support this position, showing that the actors in the joint Simon task monitor the proportion of compatible trials for their own part but not for their co-actor’s part ( Yamaguchi et al, 2018 ) and that the actors in a joint task-switching setting do not monitor the task that their co-actor has performed on a preceding trial ( Wenke et al, 2011 ; Yamaguchi et al, 2017b ). Such task monitoring appears to occur under specific conditions ( Dudarev and Hassin, 2016 ; Liefooghe, 2016 ; Yamaguchi et al, 2017a ). Therefore, the actors may only represent limited aspects of the co-actor’s part of the task, and they divide the labor of the joint task, eliminating an additional burden monitoring their co-actor’s part of the task.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has experienced increased interest in the psychological basis of social coordination and joint action (e.g., Knutsen & LeBigot, 2018;Müller et al, 2011;Sebanz, Bekkering, & Knoblich, 2006;Yamaguchi, Wall, & Hommel, 2017, 2018. This interest was sparked by theoretical considerations that the ability to act jointly with others is fundamental for human social life (e.g., Bratman, 1992;Gilbert, 2009) and lies at the basis of human cultural evolution (Habermas, 1985;Richerson & Boyd, 2005).…”
Section: Introductionmentioning
confidence: 99%